PENERAPAN MODEL BERMAIN BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN MINAT SAINS SISWA SEKOLAH DASAR - Yulianti, Dwi; Fianti, - (Lembaran Ilmu Kependidikan, 2010)
The research on the applicability of game-based Contextual Teaching andLearning (CTL) model on a simple instument problem aims to find out the increase ofthe interest and and achievement of learning science, the response of students andteachers to the application of the models. Classroom action research was conducted inthree cycles. The data of the improvement of interest in learning science and thestudents and teachers responses were obtained through a questionnaire. Thecognitive result of the study was obtained through an achievement test. The affectiveand psychomotor results of the study were obtained through an observation. The resultcan be concluded that the application of game-based Contextual Teaching andLearning (CTL) model increased the interest and learning outcomes.Kata kunci: Contextual teaching and learning (CTL), sains, minat